Duality and degeneracy lifting in two-dimensional electron liquids on SrTiO3(001) - Igor Sokolović; Eduardo B. Guedes; Thomas P. van Waas; Fei Guo; Samuel Poncé; Craig Polley; Michael Schmid; Ulrike Diebold; Milan Radović; Martin Setvín; J. Hugo Dil (Nature Communications)
Abstract Two-dimensional electron liquids (2DELs) have increasing technological relevance for ultrafast electronics and spintronics, yet significant gaps in their fundamental understanding are exemplified on the prototypical SrTiO3. We correlate the exact SrTiO3(001) surface structure with distinct 2DELs through combined microscopic angle-resolved photoemission spectroscopy and non-contact atomic force microscopy on truly bulk-terminated surfaces that alleviate structural uncertainties inherent to this long-studied system. The SrO termination is shown to develop a 2DEL following the creation of oxygen vacancies, unlike the intrinsically metallic TiO2 termination. Differences in degeneracy of the 2DELs, with nearly the same band filling and identical band bending, are assigned to polar distortions of the Ti atoms in combination with spin order, supported with the extraction of fundamental electron-phonon coupling strength. These results not only resolve the ambiguities regarding 2DELs on SrTiO3 thus far, but also pave the way to manipulating band filling and spin order in oxide 2DELs in general.